Menyoal Moratorium Sawit : Prospek dan Tantangan - Nabila Luthvita Rahma; Muhammad Amien Rois; Amalya Nur Hidayah (Program Studi Hukum Keluarga Islam, 2022)
The government's policy of issuing Presidential Instruction Number 8 of 2018 concerning Suspension and Evaluation of Oil Palm Plantation Permits and Improvement of Oil Palm Plantations can be interpreted as a step in structuring oil palm plantations in Indonesia as well as providing legal certainty. This paper aims to determine the achievements of the palm oil moratorium based on the Presidential Instruction Number 8 of 2018 and to find out the prospects and challenges faced by the government in implementing the palm oil moratorium program. To answer these problems, this paper uses a statutory approach, a case approach, and a conceptual approach. While the data sources used are secondary data in the form of Presidential Instruction Number 8 of 2018 and others. The results of this study can be concluded that the implementation of the Presidential Instruction regarding the Palm Oil Moratorium has positive implications, especially in preventing the rate of deforestation. The prospect of implementing a palm oil moratorium based on Presidential Instruction Number 8 of 2018 has achieved a conducive business climate and resolved overlapping problems related to palm oil business permits. In addition to these prospects, the government also faces difficult challenges, namely the potential for agrarian conflicts that are still high and law enforcement in a sustainable manner in the oil palm plantation sector it self.Kebijakan pemerintah menerbitkan Instruksi Presiden Nomor 8 Tahun 2018 tentang Penundaan dan Evaluasi Perizinan Perkebunan Kelapa Sawit serta Peningkatan Perkebunan Kelapa Sawit dapat dimaknai sebagai langkah dalam penataan perkebunaan sawit di Indonesia sekaligus memberikan kepastian hukum. Tulisan ini bertujuan untuk mengetahui capaian moratorium sawit berdasarkan Instruksi Presiden Nomor 8 Tahun 2018 dan untuk mengetahui prospek dan tantangan yang dihadapi pemerintah dalam menjalankan program moratorium sawit. Untuk menjawab permasalahan tersebut tulisan ini menggunakan metode pendekatan perundang-undangan, pendekatan kasus, serta pendekatan konseptual. Sedangkan sumber data yang digunakan yaitu data sekunder berupa Instruksi Presiden Nomor 8 Tahun 2018 dan lainnya. Hasil kajian ini dapat disimpulkan bahwa pemberlakuan Instruksi Presiden tentang Moratorium Sawit membawa implikasi positif terutama dalam mencegah laju deforestasi. Prospek dari pemberlakuan moratorium sawit berdasarkan Instruksi Presiden Nomor 8 Tahun 2018 telah tercapainya iklim usaha yang kondusif dan menyelesaikan permasalahan tumpang tindih terkait izin usaha sawit. Selain prospek tersebut pemerintah juga menghadapi tantangan yang tak mudah yakni potensi konflik agraria yang masih tinggi dan penegakan hukum secara berkelanjutan di bidang perkebunan kelapa sawit itu sendiri.